PROFESIONALISME, KOMITMEN ORGANISASI, INTENSITAS MORAL DAN TINDAKAN AKUNTAN MELAKUKAN WHISTLEBLOWING - Setiawati, Luh Putu; Sari, Maria M. Ratna (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
Cheating on the leading companies happened lately. Whistleblowing deemed necessary to minimize fraud within the company. Factors of the actions of accountants to do whistleblowing are professionalism, organizational commitment and moral intensity. The purpose of this study to obtain empirical evidence of the influence of professionalism, organizational commitment, and moral intensity on whistleblowing. The sampling method is non-probability sampling. This study used multiple linear regression analysis. The results showed professionalism, organizational commitment, and moral intensityhave a positive influence.. It means better professionalism, organizational commitment and moral intensity the higher the intention accountant to do whistleblowing.
Keywords: professionalism, organizational commitment and moral intensity, accountants, intention of the accountants to do whistleblowing